Crosslinking as a treatment for infectious crystalline keratopathy - S. V. Trufanov; I. A. Riks; S. S. Papanyan; M. Ezugbaya; R. Boutaba (Российский офтальмологический журнал, 2022)
Infectious crystalline keratopathy (ICK) is a rare cornea disease, manifested by gray-and-white tree-like or needle-like stromal opacities with minimal signs of inflammation. The disease is caused by the colonization of microorganisms on the corneal stroma and their formation of biofilms, making them extremely resistant to treatment with antibiotics and to the immune response of the patient. Typically, the most important risk factor for ICK development is the presence of an immunodeficiency cornea condition with long-term topical steroid therapy, which is normally prescribed after keratoplasty. Two clinical cases of ICK are discussed in which the reduction of topical glucocorticoids and the intensive use of antibiotics did not result in positive clinical changes. Only after an accelerated crosslinking procedure (PACK-CXL), needlelike opacities disappeared in the area of microbial invasion and signs of infiltration appeared, indicating the restoration of the local immune response. This phenomenon is likely due to the destruction of the biofilm and the microbial agents themselves, which afterwards contributed to a more effective impact of the antibacterial drug. This combined treatment led to resorption of the inflammatory focus with the formation of local opacification. The effectiveness of PACK-CXL in infectious processes is explained by the effects of both riboflavin and ultraviolet radiation. No literature references on the use of cross-linking in the treatment of ICK are available. In our opinion, cross-linking in early ICK patients after keratoplasty is justified by the inability, in some cases, to completely discontinue glucocorticosteroid therapy, as this will greatly increase the chances of rejection and graft jailure. PACK-CXL can be an effective way of destroying the biofilm in the corneal stroma.